2020
DOI: 10.1186/s12898-020-00337-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of habitat edges on vegetation structure and the vulnerable golden-brown mouse lemur (Microcebus ravelobensis) in northwestern Madagascar

Abstract: Background Edge effects can influence species composition and community structure as a result of changes in microenvironment and edaphic variables. We investigated effects of habitat edges on vegetation structure, abundance and body mass of one vulnerable Microcebus species in northwestern Madagascar. We trapped mouse lemurs along four 1000-m transects (total of 2424 trap nights) that ran perpendicular to the forest edge. We installed 16 pairs of 20 m2 vegetation plots along each transect and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 58 publications
0
12
0
3
Order By: Relevance
“…Comparison with the results of previous studies, revealed that edge effects can vary on the type of edge habitat space adequacy by primate populations. Such ecological change capacity could be particularly relevant for reducing species responses to habitat loss and anthropogenic disturbance (Andriatsitohaina et al, 2020). In Javan Gibbon populations there tends to be an edge effect because the http://eduvest.greenvest.co.id habitat has been fragmented and the edge effect has increased.…”
Section: Figure 2 Slices Of Species Similarity Bird Species Between P...mentioning
confidence: 99%
“…Comparison with the results of previous studies, revealed that edge effects can vary on the type of edge habitat space adequacy by primate populations. Such ecological change capacity could be particularly relevant for reducing species responses to habitat loss and anthropogenic disturbance (Andriatsitohaina et al, 2020). In Javan Gibbon populations there tends to be an edge effect because the http://eduvest.greenvest.co.id habitat has been fragmented and the edge effect has increased.…”
Section: Figure 2 Slices Of Species Similarity Bird Species Between P...mentioning
confidence: 99%
“…As forests are broken into smaller, isolated patches, the boundaries between these fragments become critical zones of change. These edges often exhibit altered microclimates, increased vulnerability to predation, and disruptions in habitat structure (Andriatsitohaina et al, 2020). Some species may thrive in these edge habitats, while others struggle to adapt.…”
Section: Diversity Of the Forest With Herpetofauna Distributionmentioning
confidence: 99%
“…The overall result is a complex interplay of species shifts, reduced genetic diversity, and potential declines in animal populations. To conserve and enhance faunal diversity in fragmented landscapes, it is essential to understand and mitigate these edge effects through thoughtful conservation planning and habitat management strategies (Andriatsitohaina et al, 2020). In the study of WRR, edge effects were particularly pronounced, revealing how herpetofauna diversity suffered along the forest edges.…”
Section: Diversity Of the Forest With Herpetofauna Distributionmentioning
confidence: 99%
“…Many species are attracted to edge environments that have complementary resources provided by different habitats or the occurrence of rare resources from either habitat [ 37 , 38 ]. For instance, lemurs may reside near or move to forest edges to opportunistically use plant resources [ 39 ]. Variability in resources is a primary reason why richness is often higher along the edges of fragmented habitats (e.g.…”
Section: Introductionmentioning
confidence: 99%